Corpus stylistics in contemporary English dramas : keywords and semantic fields of delusions - Kriangkrai Vathanalaoha, (Penerbit Universiti Kebangsaan Malaysia, 2022)
As reflected through contemporary Anglo-American dramas, delusion is considered a repertoire afflicted by the societal depression after World War II. Since post-war depression can be vocally expressed, it poses a question of how the theme of delusion could be portrayed through emotive phrases and how they are interconnected with the literary themes in dramas. This study investigates semantic fields demonstrated through corpus-based methodologies on a collection of contemporary dramas via Lancsbox and Wmatrix. Ten contemporary British and American dramas are constructed as a specialized corpus to compare with the reference corpus, built upon BNC and COCA imaginative texts. The comparison can generate keywords, lexical bundles, shared collocates, and extract the words indicating what the specialized corpus is about, or “aboutness.” The meta-tiered results show that “Negative,” “Wanted,” “Getting and possession,” and “Diseases” are the fields that relate to the aboutness of the contemporary dramas. The top 20 keywords can refer to the specialized corpus’s dialogic structure and highlight four characters with dilemmas regarding the delusional disorder. The collocation network, measured by GraphColl, can raise stylistic awareness where these keywords and semantic fields are interconnected and substantiate the theme of delusion. Though literary texts are interpreted through close reading, this study argues that quantitative and qualitative aspects can be integrated to undermine the absence of positivism.